Correspondence as a documentary form, its persistent representation, and email management, preservation, and access. (16th March 2015) - Zhang, Jane
Abstract : Purpose: – The aim of this paper is to construct a systematic way of thinking about correspondence as a documentary form and discuss the role its persistent representation features play in management, preservation and access of email correspondence. Design/methodology/approach: – Using the method of diplomatic analysis as a guiding theory, the paper conducts a historical review of correspondence recordkeeping and email systems in the American context, analyzes the evolution of its persistent representation features and discusses the implications on current email management and archival practices. Findings: – Correspondence as a document form and its persistent representation features have played an important role in traditional correspondence recordkeeping and electronic mail management. The design of systems to manage, preserve and access email records should reflect the characteristics and functionality of email records, capable of retaining email correspondence as a documentary form supported by its persistent representation features. Research limitations/implications: – The research in this paper mostly covers secondary sources with a regional focus. The analysis covers important historical developments in correspondence and email recordkeeping and archival practices. The study uses examples of email archives available online, and further research can be developed when more email archival collections are processed and constructed. Originality/value: – A systematic analysis of persistent representation of traditional correspondence and electronic mail provides a useful perspective to reflect on the characteristics of correspondence as a document form and offers some food for thought for records management and archival professionals and assists them in developing systems to better manage, preserve and provide access to email correspondence.